The phylogenetic relationships of the charismatic poster frogs, Phyllomedusinae (Anura, Hylidae) - Faivovich, Julian [UNESP]; Haddad, Celio Fernando Baptista [UNESP]; Baeta, Delio; Jungfer, Karl-Heinz; Alvares, Guilherme F. R.; Brandao, Reuber A.; Sheil, Christopher; Barrientos, Lucas S.; Barrio-Amoros, Cesar L.; Cruz, Carlos A. G.; Wheeler, Ward C. (Wiley-Blackwell, 2010)
The leaf or monkey frogs of the hylid subfamily Phyllomedusinae are a unique group of charismatic anurans. We present a molecular phylogenetic analysis that includes 45 of the 60 species of phyllomedusines using up to 12 genes and intervening tRNAs. The aims were to gain a better understanding of the phylogenetic position of Phrynomedusa, test the monophyly and explore the relationships among several putative lineages (Hylomantis, the H. buckleyi Group, Phasmahyla, the four species groups of Phyllomedusa, and the species of Phyllomedusa that remain unassigned to any group), and to examine the implications of our phylogeny for the evolution of several characters in phyllomedusines. The analyses resulted in a well-supported phylogenetic hypothesis that provides a historical framework for a discussion of the evolution of characters associated with reproductive biology, gliding behaviour, the physiology of waterproofing, and bioactive peptides. Implications include an earlier origin for eggless capsules than for leaf-folding behaviour during amplexus, two independent origins of gliding, and an earlier origin of reduction in evaporative water loss than uricotelism, which is a result that originally was predicted on the basis of physiology alone. Furthermore, our results support the prediction that bioactive peptides from different peptide families are to be expected in all species of Phyllomedusinae. Hylomantis (as recently redefined) is shown to be paraphyletic and the synonymy of Agalychnis is revised to remedy this problem by including both Hylomantis and Pachymedusa.(C) The Willi Hennig Society 2009.